Risk Profile Analysis In Determining Profit Growth: Evidence From Selected Commercial Banks In Indonesia - Achmad Nawawi; Disman Disman; Nugraha Nugraha; Ikaputera Waspada (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Financial Statement has a role to provide the information about the condition of the company. For the banking institution, the financial statement serve the information about the Non Performing Loan and Loan to Depositi Ratio as the measure of the rsik in banking industry. The aim of this study was to examine the effect of NPL (Non-Performing Loan) and LDR (Loan-to-Deposit Ratio) on profit growth in 10 bank companies during a 5-year research period. The study utilized quantitative data by using non probability sampling with random tehnique, utilizing the SPSS 21 program. The results revealed that NPL and LDR had a negative impact on profit growth. In other words, the higher the levels of NPL and LDR, the lower the profit growth will be. In conclusion, it is important for bank companies to pay attention to the level of NPL and LDR to enhance profit growth